Зовнішні загрози впливу хімічних речовин на безпеку АЕС - Holovko, V.; Petropavlovskiy, E. (State Scientific and Technical Center for Nuclear and Radiation Safety, 2008)
The approaches to analysing external hazard of chemical agents impact were presented in the framework of NPP Safety Analysis Reports preparation.